2013
DOI: 10.1021/la401371c
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Solutions of Organic Conductive Nanoparticles

Abstract: Although molecular metals have been known for decades, their insolubility, low vapor pressure, and synthesis routes have prevented them from being integrated into electronic devices. We have prepared stable colloidal solutions of the organic metal TTF-TCNQ that overcome such difficulties. The solutions contain well-dispersed nanoparticles stabilized by long alkyl chain amines. They afford soluble powders by evaporation and homogeneous thin films by drop-casting. Powders and films show room temperature conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 29 publications
(44 reference statements)
1
44
0
Order By: Relevance
“…sticks and nanopowder) do not influence the thermal behavior of both materials. Moreover, the investigated materials are thermally stable up to 180-190 °C, which is in good agreement with the results of de Caro et al [15].…”
Section: Characterization Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…sticks and nanopowder) do not influence the thermal behavior of both materials. Moreover, the investigated materials are thermally stable up to 180-190 °C, which is in good agreement with the results of de Caro et al [15].…”
Section: Characterization Methodssupporting
confidence: 92%
“…The amphiphilic molecule, acting as a stabilizing agent, controlled the particle growth through coordination to the metal centre. We have recently shown that octylamine could also stabilize 40 nm-TTFTCNQ nanoparticles, in which TCNQ-OA (TCNQ whose a CN group has been substituted by an amino group) molecules were present at the particles surface and were responsible for their stabilization and their dispersibility in common organic solvents [15]. Furthermore, we have recently published the preparation of (TMTSF) 2 ClO 4 nanocrystals (TMTSF: tetramethyltetraselenafulvalene) using the electrocrystallisation technique in the presence of N-octylfurfuryl-imine ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research focuses on their preparation in forms transferable onto surfaces, and on the study of the consequences of the final morphology on physical properties. For example, colloidal solutions of TTF-TCNQ NPs (TCNQ = tetracyanoquinodimethane) offer promising applications, [7] a chemistry-based technique for patterning films of (BEDT-TTF) 2 I 3 on a polymeric substrate was described, [8] and surface-selective deposition of TTF-TCNQ, TTF[Ni(dmit) 2 ] 2 , and (BEDT-TTF) 2 I 3 NPs was applied to the construction of organic transistor structures.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Temperature dependency of the resistance of a fiber-like shown that the preferred morphology of TTF[Ni(dmit) 2 ] 2 is elongated in the majority of molecular conductors: single crystals are needle-like and most thin films are made of microfibers. The growth of this phase and that of other molecular conductors as spherical nanoparticles was a synthesis challenge, which the "Molecules and Materials" team addressed successfully by adding stabilizing molecules to the reaction medium[46,89].…”
mentioning
confidence: 99%
“…We have developed methods for preparing molecular conductors as nanoparticles because they can be stored and used directly better as suspensions or as colloidal solutions when preparing films or composite materials.Colloidal solutions were prepared successfully with two conducting materials: TTF-TCNQ[89,97] and nickel ethylene tetrathiolate polymers[98]. We obtained stable dispersions of TTF[Ni(dmit) 2 ] 2 as well as other molecular conductors and superconductors, particularly Bechgaard salts[99] and (BEDT-TTF) 2 I 3[46].…”
mentioning
confidence: 99%